Global perspectives on financial inclusion : case studies in microfinance and women's empowerment - Malhotra, Nishi (Emerald Publishing Limited, 2025)
The United Nations Sustainable Development Goals (UN SDGs) place a strong emphasis on empowering women and reducing poverty. To achieve these goals effectively, it is essential to implement strategic initiatives that connect policy planning with practical solutions. Microfinance has played a significant role in enabling the financial inclusion of women through collective and joint liability models. While these collective initiatives have existed worldwide in various forms, there remains a noticeable lack of literature on collectives and joint liability initiatives supporting semi-formal finance, especially in emerging economies.